Clojure for Data Science - Henry Garner (Packt Publishing, 2015)
In "Clojure for Data Science," you'll explore how to leverage the powerful Clojure programming language for data analysis, machine learning, and statistical computation. This book is designed to guide you through implementing robust solutions to data science challenges efficiently and effectively using Clojure's unique features.What this Book will help me doDevelop confidence in performing statistical analysis on data to derive meaningful conclusions.Master key machine learning techniques including regression, classification, and clustering.Learn to utilize distributed computing frameworks such as Spark and Hadoop with Clojure.Gain the ability to process and analyze different types of data including text, graphs, and time-series data.Enhance your skills in creating interactive visualizations and integrating data science models into production systems.Author(s)None Garner is a seasoned software developer and data scientist with extensive experience in using the Clojure programming language. With a passion for teaching practical applications of programming in data science, they are dedicated to helping practitioners master complex concepts. Their clear and engaging writing style reflects a deep understanding of the subject and a commitment to sharing knowledge.Who is it for?This book is tailored for engineers and developers who have a foundational understanding of programming and are looking to apply data science in their workflow. If you're interested in enhancing your skills in data analysis and machine learning, particularly using Clojure, this book will suit you. Additionally, data professionals who aim to work with distributed systems and need practical coding examples will benefit greatly. It's an excellent resource for intermediate and advanced developers eager to delve into data science and enhance their technical toolbox.